Adsorptive Removal of Dye from Industrial Effluents Using Natural Iraqi Palygorskite Clay as Low-Cost Adsorbent - Taha, Dakhil Nassir; Samaka, Isra’a Sadi; Mohammed, Luma Ahmed (Journal of Asian Scientific Research, 2013)
Palygorskite clay has been investigated as low cost and ecofriendly adsorbent for the removal Basic Red 2(BR-2) from aqueous solution. Batch adsorption studies are carried out by observing effect of amount of adsorbent dose, contact time, pH, initial concentration of ( BR-2) and particle size of adsorbent on the adsorption capacity of the adsorbent were studied. Adsorption data fits the Langmuir and Freundlich adsorption isotherms. The calculated value of the Langmuir parameter for adsorption capacity of the dye over the adsorbent is 200mg/g adsorbent. This study shows that natural clay is successfully used to remove the Safranin-O dye from aqueous solutions as alternative to activated carbon.